Prediksi Slippage menggunakan Metode Regresi - Berkah Hani (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2018)
slippage is important for lubricant around plunger. The accuracy slippage maximizes oil production. This paper explained several regression methods to predict slippage value. Several regression methods that is used for example Huber estimation, Ordinary Least Square, Theil-Sen Estimation, RANSAC estimation and Support Vector Machine-Regression